2008
DOI: 10.3113/fai.2008.0808
|View full text |Cite
|
Sign up to set email alerts
|

The Achillon® Achilles Tendon Repair: Is it Strong Enough?

Abstract: The Achillon repair appears to be a biomechanically sound method of repair for the acutely ruptured Achilles tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
1
39
1
1
Order By: Relevance
“…Ismail et al [10] Latendresse et al [12] compared the repair of Xexor digitorum profundus tendon with single micro-Mitek™ anchor (Mitek, Westwood, MA) to a modiWed Bunnell two-strand pullout technique using a monoWlament or a braided polyester suture. They found greater gap formation with monoWlament sutures compared with the braided polyester sutures with both repair techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al [10] Latendresse et al [12] compared the repair of Xexor digitorum profundus tendon with single micro-Mitek™ anchor (Mitek, Westwood, MA) to a modiWed Bunnell two-strand pullout technique using a monoWlament or a braided polyester suture. They found greater gap formation with monoWlament sutures compared with the braided polyester sutures with both repair techniques.…”
Section: Discussionmentioning
confidence: 99%
“…15,31 We feel this is also pertinent when evaluating studies of open versus percutaneous techniques, as many percutaneous techniques employ a six-stranded repair versus the four strands utilized in the open repairs. 12,14,19 There are numerous different suture techniques that can be utilized for tendon repair. Gebauer et al showed that the Bunnell repair was stronger than the Kessler repair.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Some authors recommend surgery for young and physically active patients, 6,7 but although open and minimally invasive techniques have been used, few studies have examined the biomechanical characteristics of different configurations of sutures and the quality of repair using these techniques. [8][9][10][11][12] Early weight-bearing mobilisation and strengthening exercises are increasingly being used to accelerate recovery and time of return to sport. [13][14][15][16][17] Therefore, strong repairs should resist distraction, allowing early rehabilitation and promoting tendon healing.…”
mentioning
confidence: 99%